Combination therapy of sorafenib and drug-eluting bead transarterial chemoembolization for advanced hepatocellular carcinoma with and without hepatic arteriovenous shunt. Issue 4 (8th February 2022) - Chen, Pin-Ko; Chiu, Sung-Hua; Tsai, Ming-Ting; Chang, Kai-Hsiang; Chang, Wei-Chou; Lin, Hsuan-Hwai; Lo, Cheng-Hsiang; Huang, Guo-Shu; Chang, Ping-Ying
Abstract : Background: To compare the efficacy and safety of combination therapy with sorafenib and drug-eluting bead transarterial chemoembolization (DEB-TACE) in advanced hepatocellular carcinoma (HCC) with or without hepatic arteriovenous shunt (HAVS). Methods: This retrospective, single-center study enrolled 59 advanced HCC patients treated with combination therapy, of whom 33 (55.9%) patients had HAVS. Tumor response according to the mRECIST criteria was evaluated based on the CT images 1 month after TACE, and changes in the arterial enhancement ratio (AER) of tumors and portal vein tumor thrombosis were also documented. Time-to-progression (TTP), overall survival (OS), and prognostic factors were analyzed. Safety was evaluated with the incidence of TACE-related complications within 6 weeks after TACE. Results: The tumor response between the two groups showed no significant difference in the objective response rate (69.2% in the group without HAVS vs 60.6% in the group with HAVS, p = 0.492) or disease control rate (92.3% vs 87.9%, p = 0.685). The two groups showed comparable TTP (4.23 vs 2.33 months, p = 0.235) and OS (12.77 vs 12.97 months, p = 0.910). A drop in the AER of tumors of more than 20% on post-TACE CT independently predicted better OS. With regard to safety, there was no significant difference between the two groups. Conclusion: For advanced HCC, combination therapy had equal efficacy and safety in patients with HAVS compared to those without HAVS, indicating that DEB-TACE is an optional and effective treatment in these patients.